Microtubules and Microfibrils in Human Platelets - Sixma, J. J; Molenaar, I (Thrombosis and Haemostasis, 1966)
The microtubules and microfibrils of human platelets are described. They are studied under conditions that give as little alterations as possible. Conclusions on their localisation in vivo are drawn and their possible role in maintaining the platelet shape is discussed.